OP0091 Prediction of radiographic spinal progression using biomarkers in patients with ankylosing spondylitis who are at high risk for progression. (23rd January 2014) - Poddubnyy, D.; Conrad, K.; Ruiz-Heiland, G.; Syrbe, U.; Haibel, H.; Appel, H.; Rudwaleit, M.; Schett, G.; Sieper, J.
Abstract : Background: Presence of radiographic spinal damage (syndesmophytes) is the strongest predictor of further radiographic progression in ankylosing spondylitis (AS). In the recent years several biomarkers have been found to be associated with radiographic spinal progression/syndesmophyte formation in AS, however, it is not clear, whether these biomarkers are also able to predict new bone formation in AS patients who are at high risk of radiographic progression due to a presence of syndesmophytes at baseline. Objectives: To investigate the association of biomarkers with radiographic progression in the spine (new syndesmophytes formation or growth of the existing syndesmophytes) in patients with AS and risk factors for such progression. Methods: Altogether 64 patients with AS from the German Spondyloarthritis Inception Cohort (GESPIC) were considered to be eligible for this analysis due to the presence of syndesmophytes at baseline. Radiographs of the lumbar and cervical spine performed at baseline and after 2 years of follow-up were scored independently by two trained readers. Two groups of patients were defined according to the scoring results: Group I (progressors, n=26) patients with syndesmophytes at baseline and new syndesmophyte or syndesmophytes growth after 2 years; Group II (non-progressors, n=38): patients with syndesmophytes at baseline but without progression after 2 years. Serum levels of the following biomarkers were examined: C-reactive protein (CRP), matrix metalloproteinase 3 (MMP3), sclerostin, Dickkopf 1 (DKK1), periostin, bone morphogenetic protein (BMP)2 and 7, osteoprotegerin (OPG), vascular endothelial growth factor (VEGF), procollagen type I and II N-propeptide (PINP and PIINP), CTX-II, BALP, sRANKL, COPM, and bone sialoprotein. Results: There were statistically significant differences between Group I and Group II in the baseline serum levels of CRP (17.1±17.1 vs 8.7±9.9, p=0.031) and MMP3 (40.2±36.2 vs 19.5±23.2, p=0.016) that confirmed a predictive value of markers of active inflammation regarding radiographic spinal progression. However, in patients with both risk factors, syndesmophytes and elevated CRP at baseline, serum levels of MMP3, BMP2, PIINP, VEGF, and OPG demonstrated statistically significant inter-group differences (table). Protective trends were found also for sclerostin, DKK1 and periostin. No significant differences in serum levels were found for other tested biomarkers. Conclusions: Here we were able to show for the first time that higher levels of MMP3, BMP-2, PIINP, and VEGF, and lower level of OPG might predict progression of structural damage in the spine in patients with AS who are already at high risk of such a progression due to the presence of syndesmophytes and elevated CRP. Disclosure of Interest: None Declared